Industrial supply chains as an opportunity for modern organizations - Dendera-Gruszka, Małgorzata; Kulińska, Ewa; Masłowski, Dariusz (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The article presents an analysis of the concept of supply chains and studies on the industry supply chain. The literature analysis revealed theories of supply chains on a theoretical basis, which enabled the development of a supply chain concept dedicated to a specific industry – heavy industry. The purpose of the article was to present the industry supply chain for the heavy industry sector. The research methodology was based on an analysis of the heavy industry sector in 2016–2019, an interview and literature analysis of previously known concepts of supply chains.